Relationship Between COPD Progression and Frailty Progression: A Five-year Observation in Real Clinical Practice - Nishimura K; Kusunose M; Shibayama A; Nakayasu K (International Journal of COPD)
Koichi Nishimura,1,2 Masaaki Kusunose,3 Ayumi Shibayama,4 Kazuhito Nakayasu5 1National Center for Geriatrics and Gerontology, Obu, Aichi, Japan; 2Clinic Nishimura, Ayabe, Kyoto, Japan; 3Department of Respiratory Medicine, National Center for Geriatrics and Gerontology, Obu, Aichi, Japan; 4Department of Nursing, National Center for Geriatrics and Gerontology, Obu, Aichi, Japan; 5Data Research Section, Kondo Inc., Osaka, JapanCorrespondence: Koichi Nishimura, Clinic Nishimura, 4-3. Kohigashi, Kuri-cho, Ayabe, 623-0222, Japan, Tel +81-773-47-0321, Fax +81-773-47-0201, Email koichinishimura1@gmail.comPurpose: Although a cross-sectional association between frailty and chronic obstructive pulmonary disease (COPD) has been established, the longitudinal relationship between the progression of both frailty and COPD remains unclear.Materials and Methods: This longitudinal study followed 87 COPD patients over five years, with evaluations conducted every six months. Participants underwent pulmonary function tests and completed the Kihon Checklist, a tool widely used in Japan to assess frailty. Kihon Checklist scores range from 0 (no frailty) to 25 (severe frailty), categorizing participants as robust (0– 3), pre-frail (4– 7), or frail (8– 25). Annual changes were analyzed using linear mixed models.Results: A significant association was observed between time and worsening frailty classification, with patients transitioning from robust to pre-frail or from pre-frail to frail (odds ratio: 1.224, p = 0.004). However, the GOLD stages (GOLD 1 to GOLD 4) did not exhibit significant progression over five years. The cohort demonstrated significant declines in forced expiratory volume in one second (FEV1) and increases in Kihon Checklist total scores. FEV1 decreased by an estimated mean of 28.6 mL per year (95% CI: 18.9– 38.4, p < 0.001), while the Kihon Checklist total score increased by 0.30 annually (95% CI: 0.09– 0.51, p = 0.006). Estimated FEV1 declined significantly from baseline after two years in the baseline frail group (p < 0.01), after 3.5 years in the pre-frail group (p < 0.01), and after four years in the robust group (p < 0.05). Although the GOLD 3+4 group showed a significant increase in Kihon Checklist total scores after 3.5 years (p < 0.05), no significant change was observed in the GOLD 1 and GOLD 2 groups.Conclusion: COPD patients with frailty show a more rapid decline in FEV1, indicating accelerated COPD progression. These findings suggest frailty is static and only COPD is progressing.Keywords: disease progression, Kihon Checklist, linear mixed models